Routine fetal echocardiography for detection of congenital heart disease-mandatory or an optional tool? - Gupta, Tanvi; Ganjoo, Sandesh; Kaul, Varun; Makhija, Rashmi Khilnani; Mishra, Smita; Sareen, Sugandh (International Journal of Contemporary Pediatrics, 2023)
Background: Aim of the study was to assess the role of fetal echocardiography in identification of antenatal cardiac defects in a tertiary care centre in North India. Methods: Prospective study done in a tertiary care centre in North India on female patients presenting to a tertiary care centre with pregnancy over a period of two years. All routine investigations were done and specific examination in the form of a screening fetal echocardiography was done in the selected two groups of patients, high and low risk. Results: A sample size of 250 patients with intrauterine pregnancy of 18-28 weeks of gestation was analyzed. A detailed history, examination and fetal echocardiography was performed in all the patients. In group I-105 patients with elevated risk factors (for congenital heart disease) (CHD) were included whereas in group II-145 patients with low risk factors were taken. The various demographic parameters among the two groups were almost similar. The outcome was also similar in two groups with nil neonatal mortality. Except for the NICU admission between the two groups, rest all the parameters whether maternal or neonatal were not statistically significant. Conclusions: In the present study, we tried to find out role of fetal echocardiography for detection of CHD in high and low risk cases. The results were almost similar in both high and low risk group. Indications of referral for fetal echocardiography cannot be listed as it was found that almost similar percentage of heart defects are seen in both groups I and II.